KAJIAN PUTUSAN BEBAS TERHADAP TERDAKWA PELAKU TINDAK PIDANA NARKOTIKA: STUDI KASUS DI PENGADILAN TINGGI DKI - Sitorus, Hotman (E-Journal Widya Yustisia, 2017)
The case of free decision in the High Court against the defendants appeal from DKI perpetrators of crime Narcotics based on decisions of the District Court of first instance in East Jakarta appeals for review. The purpose of this article is to discuss and find out: (1) the reason why the defendant submits the efforts of appeal, (2) to know the basic consideration of the High Court judges over the decision of the District Court in East Jakarta. The research methods used are normative and descriptive exploratory approach. The results showed that: (1) the defendant's appeal because it he found not guilty and refused to accept the decision of the first level District Court in East Jakarta (2) the consideration of the High Court judges over the decision of the District Court in East Jakarta is, that Article 189 paragraph, 4 of the Code of Criminal Procedure States: Description of the defendant alone is not enough to prove that he is guilty of committing acts that accused him but must be accompanied by new evidence. the High Court argued" the defendant did not know the contents of the Envelope the Yoke for submission to Lukman Hakim ". Therefore the defendant has to be acquitted of all charges, the public prosecutor's.